Incorporation of arch action in grade beams - Murty, D. S. R.; Latha, K. (Journal of Structural Engineering, 2025)
In reinforced concrete framed structures and large industrial buildings with reinforced concrete or steel columns with pedestals and suspended floors, the column bases are connected by reinforced concrete beams in the vicinity of basement level. These are called grade beams or plinth beams. The beams serve two purposes. First, grade beams bear the loads of ground floor, such as peripheral enclosing walls and slab loads in suspended floors. Second purpose served is, that grade beams reduce slenderness of ground floor columns. Like other beams in the structure, grade beams are straight and horizontal. Slight arching of the grade beams in the vertical plane results in substantial economy in their design. This paper presents experimental evidence of improved strength, performance and significant economy in steel reinforcement and concrete, when grade beams are slightly arched. The arch rises of the two hinged circular arch grade beams adopted in the test programme were 133mm, 181mm and 221mm. All the arch beams with different rises demonstrated economy by 25% in concrete and more than 80% in steel reinforcement. Even the arch grade beam with the minimum rise showed better strength, performance and serviceability criteria than the companion straight beam.